Allelic polymorphism of KIR2DL2/2DL3 in a southern Chinese population. Issue 5 (1st October 2015) - Zhen, J.; He, L.; Xu, Y.; Zhao, J.; Yu, Q.; Zou, H.; Sun, G.; Deng, Z.
Abstract KIR2DL2 and KIR2DL3 segregate as alleles of the same killer cell immunoglobulin‐like receptor (KIR) gene locus. They have been associated with viral infectious diseases and certain cancers and their allelic information may help to better comprehend mechanisms. The allelic polymorphism of KIR2DL2/2DL3 has been shown to influence their binding specificity and affinity to the HLA‐C1 ligands. The present study aims to investigate the distribution of the allelic polymorphism of KIR2DL2/2DL3 in a southern Chinese population using sequence‐specific primer polymerase chain reaction (PCR‐SSP) and PCR‐sequence‐based typing (SBT) at the entire coding sequence. Of the 306 tested individuals, 1.96% were positive for KIR2DL2 only, 78.10% for KIR2DL3 only, and 19.93% for both KIR2DL2 and 2DL3. KIR2DL3 showed a high degree of diversity in the study population with 15 alleles detected including 8 novel ones. The predominant 2DL3 allele in the study population is 2DL3*00101 (92.81%) followed by 2DL3*00201 (24.18%), 2DL3*023 (4.25%), and 2DL3*00109 (1.31%). The remaining 11 2DL3 alleles all had a frequency below 1%. Three detected 2DL2 alleles were 2DL2*00301 (18.95%), 2DL2*00101 (3.59%), and the novel 2DL2*013 (0.33%). These results provide further insight into the KIR gene diversity in Southern Chinese and may help to better understand the role played by KIR genes in associated diseases.